Glycated hemoglobin levels in patients with chronic periodontitis - Velásquez Machuca, Victor Eder (2016)
Objective: To evaluate the correlation between the level of glycosylated hemoglobin and the presence of chronic periodontitis. Materials and method: 77 patients, were grouped according to whether or not chronic periodontitis. Data were collected where took it age, gender, body mass index (BMI) and a history of dyslipidemia, periodontal chart were written to set membership group of patients, they were sent to clinical laboratory to collect and process glycosylated hemoglobin samples. All signed informed consent. Results: HbA1c was 5.58% for chronic periodontitis group, and 5.31% for no periodontitis group, unadjusted values, determined it there was statistically significant difference (P = 0.000). Taking the risk variables it was obtained no statistical influence of gender or BMI. Even considering these risk factors, it remained significant difference (P = 0.001). No significant differences were found (P = 0.921) among men (5.58%) and women (5.60%) with chronic periodontitis. In the group of patients without chronic periodontitis there is no significant difference (P = 0.230) between males (5.33%) and women (5.29%). Conclusions: A statistically significant difference was found in the percentage of Hemoglobin and the presence of chronic periodontitis. No significant difference was found in patients according to gender, both in the group with chronic periodontitis, such as those without chronic periodontitis. The analysis of risk factors showed that the causes of the high levels of percentage of Hemoglobin were the presence of chronic periodontitis, patient age and the presence of dyslipidemia, but not gender and Body Mass Index (BMI).